Sertifikat sebagai Alat Bukti Hak Atas Tanah dalam Proses Peradilan - Ilyas Ismail (Universitas Syiah Kuala, 2011)
ABSTRACT: Based on Article 19 (2) of the Act Number 5, 1960 nd Article 32 of the Government Regulation Number 24, 1997 state that in registering land, the certificate of land functioning as a strong evidence. Whether a freehold right can only be proved by a certificate, and to that extent of such evidence in judicial process. In terms of obtaining the answers from the questions, library research is conducted by exploring, discussing and analysing the laws, research reports and relevant experts views. The findings show that such freehold right certificate is issued by National Land Authority by registration process. If there is a land without certificate hence it can be proved through witnesses statements, prediction, acknowledgemen and oath. The certificate has the strong and complete power of proving can only be admitted if there is no challenge before the court. The challenge towards the certificate can be done if there are a defect on issuing it, good faith of the holder and/or the right holder does not really own the land. A Certificate of Land as an Evidence of Land in Judicial System